Influenza Vaccine: An Engineering Vision from Virological Importance to Production - Demirden, S. Furkan; Alptekin, Kadir; Kimiz-Gebologlu, Ilgin; Oncel, Suphi S. (Biotechnology and bioprocess engineering, 2022)
According to data from the World Health Organization (WHO) every year, millions of people are affected by flu. Flu is a disease caused by influenza viruses. For preventing this, seasonal influenza vaccinations are widely considered the most efficient way to protect against the negative effects of the flu. To date, there is no “one-size-fits-all” vaccine that can be effective all over the world to protect against all seasonal or pandemic influenza virus types. Because influenza virus transforms its genetic structure and it can emerges as immunogenically new (antigenic drift) which causes epidemics or new virus subtype (antigenic shift) which causes pandemics. As a result, annual revaccination or new subtype viral vaccine development is required. Currently, three types of vaccines (inactivated, live attenuated, and recombinant) are approved in different countries. These can be named “conventional influenza vaccines” and their production are based on eggs or cell culture. Although, there is good effort to develop new influenza vaccines for broader and longer period of time protection. In this sense these candidate vaccines are called “universal influenza vaccines”. In this article, after we mentioned the short history of flu then virus morphology and infection, we explained the diseases caused by the influenza virus in humans. Afterward, we explained in detail the production methods of available influenza vaccines, types of bioreactors used in cell culture based production, conventional and new vaccine types, and development strategies for better vaccines.